2007
DOI: 10.1194/jlr.m700056-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol efflux via HDL resecretion occurs when cholesterol transport out of the lysosome is impaired

Abstract: Recently, we showed that holo HDL particle uptake and resecretion occur in physiologically relevant cell lines and that HDL uptake is mediated by scavenger receptor class B type I (SR-BI). Furthermore, we established that HDL resecretion is accompanied by [ 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…In support of this hypothesis, previous studies have successfully shown that the antiviral activity of chloroquine against several caliciviridae, another family of RNA viruses, occurs through chloroquine's ability to inhibit cathepsin L 71 . Furthermore, chloroquine also inhibits the transport of cholesterol out of the lysosomes, including to the plasma membrane, which would be expected to reduce the abundance, and alter the composition of membrane rafts, 72 thereby mimicking the raft alterations seen in NPC. Additionally, chloroquine has also been shown to interfere with the trimming of the N‐glycosylated side chain of ACE2, which may affect the internalization of ACE2, and subsequently, viral entry 73 .…”
Section: The Lysosomotropic Activities Of Different Drugs Undergoing mentioning
confidence: 79%
“…In support of this hypothesis, previous studies have successfully shown that the antiviral activity of chloroquine against several caliciviridae, another family of RNA viruses, occurs through chloroquine's ability to inhibit cathepsin L 71 . Furthermore, chloroquine also inhibits the transport of cholesterol out of the lysosomes, including to the plasma membrane, which would be expected to reduce the abundance, and alter the composition of membrane rafts, 72 thereby mimicking the raft alterations seen in NPC. Additionally, chloroquine has also been shown to interfere with the trimming of the N‐glycosylated side chain of ACE2, which may affect the internalization of ACE2, and subsequently, viral entry 73 .…”
Section: The Lysosomotropic Activities Of Different Drugs Undergoing mentioning
confidence: 79%
“…Sviridov et al ( 42 ) reported an antibody against the HDL-binding protein enhanced HDL uptake that was not accompanied by parallel changes in cholesterol efflux in rat hepatoma cells. In contrast, Pagler et al ( 43 ) demonstrated the involvement of HDL uptake and re-secretion in the maintenance of cholesterol homeostasis in cases of disturbed intracellular cholesterol efflux. The authors also showed that SR-BI mediated HDL endocytosis, leading to cholesterol efflux ( 44 ).…”
Section: Discussionmentioning
confidence: 95%
“…Further evidences for HDL endocytosis as a redundant pathway come from our findings in cells derived from patients with Niemann–Pick disease, where the LDL-receptor pathway and late endosomal cholesterol trafficking are impaired. In fibroblasts from these patients, HDL retro-endocytosis is still functional in maintaining cellular cholesterol homeostasis [113]. Similarly, HDL and LDL resecretion mediates cholesterol efflux in fibroblasts from patients with Tangier disease, where ABCA1 function and cholesterol efflux to apoA-I are defective (Neuhofer and Stangl, unpublished data).…”
Section: Discussionmentioning
confidence: 99%